2011
DOI: 10.5539/ass.v7n6p15
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Inpatient Satisfaction with Hospital Care in Bangladesh

Abstract: The objective of this study is to identify factors associated with satisfaction among inpatients receiving medical and surgical care for urinary, cardiovascular, respiratory, and ophthalmology diseases at Dhaka Government Medical College Hospital, Bangladesh. The data of this study is collected from 190 inpatients by using a patient judgments questionnaire covering 10 dimensions of satisfaction (appointment waiting time for doctor after admission, doctor's treatment and behavior, behavior and services of nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 25 publications
2
38
1
1
Order By: Relevance
“…In this study delivering mothers satisfactions was predicted by age, educational status, monthly income, wanted status of the pregnancy, having ANC follow up, shorter waiting time before seen by a health worker, health professionals' measure taken to assure privacy during maternal examinations, and not having previous health facility delivery experience. This finding is consistent with other studies in Africa [10,[16][17][18][19][20][21][22] Concerning participant's age, different studies indicated that older patients are generally more satisfied than younger patients. In this study, age group of 20 to 34 years old (85.2%) were more satisfied compared to participants with age group of 35-49 years who were satisfied.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study delivering mothers satisfactions was predicted by age, educational status, monthly income, wanted status of the pregnancy, having ANC follow up, shorter waiting time before seen by a health worker, health professionals' measure taken to assure privacy during maternal examinations, and not having previous health facility delivery experience. This finding is consistent with other studies in Africa [10,[16][17][18][19][20][21][22] Concerning participant's age, different studies indicated that older patients are generally more satisfied than younger patients. In this study, age group of 20 to 34 years old (85.2%) were more satisfied compared to participants with age group of 35-49 years who were satisfied.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding participants' educational status, less educated mothers have higher satisfaction than the educated one. Eighty six point one percent of the respondents who were grade 7-12 were more satisfied compared to 68.3% who had diploma and above; this is similar with the Bangladesh Ashrafun and Uddin [22][23][24][25][26][27][28] study in which less educated patients tended to have high satisfaction. One study has also found that those attaining higher educational level were not satisfied with their care [12].…”
Section: Discussionsupporting
confidence: 60%
“…Although several studies highlight the common issues e.g. lack of cleanliness of toilet or bathroom, long waiting hour, lack of quality of food as major area of dissatisfaction (Ashrafun and Uddin, 2011). My study put forward another important area of patient's grievances and dissatisfaction is the issue of consumer rights of patients.…”
Section: Patients' Satisfaction and Health Services Experiencesmentioning
confidence: 87%
“…Service providers are busy with private business, unavailability of drugs were identified as important reason for people's dissatisfaction about public health facilities (MOHFW, 2003;cited in Andaleeb et al, 2003). Another study conducted by Ashrafun and Uddin (2011) was done with a view to identify factors determining in-patient satisfaction in the hospital setting. The study findings reveal that toilet and bathroom condition, quality of food, long waiting hour etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patients who are dissatisfied with hospital meals are likely to develop malnutrition due to reduced food intake [8][9][10]. However, improvement in the quality of food services is one of the strategies that can contribute to quick recovery of inpatients [11].…”
Section: Introductionmentioning
confidence: 99%